2008
DOI: 10.1063/1.3050536
|View full text |Cite
|
Sign up to set email alerts
|

Ti x Si 1 − x O 2 optical coatings with tunable index and their response to intense subpicosecond laser pulse irradiation

Abstract: Ion-beam sputtered TixSi1−xO2 binary-oxide films of high optical quality with tunable bandgap and refractive index were produced using zone targets. The suitability of the films for high-power subpicosecond laser applications is explored by laser breakdown measurements. The observed scaling laws of the single-pulse breakdown threshold—a power law with respect to pulse duration and a linear law with respect to bandgap energy—are similar to results obtained with high-quality simple oxides. The single- and multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…Another phenomenological relation has been previously observed in titania-silica mixtures. 5 The authors concluded that internal threshold fluency of standing wave follows the observed a power law dependence on pulse duration and linear dependence on the absorption band-gap expressed in eV. This phenomenological formula has been previously reported also on pure metal oxide coatings by Mero et al: 42…”
Section: Lidt Measurementsmentioning
confidence: 65%
“…Another phenomenological relation has been previously observed in titania-silica mixtures. 5 The authors concluded that internal threshold fluency of standing wave follows the observed a power law dependence on pulse duration and linear dependence on the absorption band-gap expressed in eV. This phenomenological formula has been previously reported also on pure metal oxide coatings by Mero et al: 42…”
Section: Lidt Measurementsmentioning
confidence: 65%
“…For example, it can be used to tune the refractive index in combination with laser irradiation stability of phase shift in optical nanocomposites [65,66]. By employing plasmonic metals in dielectric or semiconducting matrices, the approach can be used to influence the lateral plasmon enhanced electric field for sensing [67] or photocatalytic [68] applications.…”
Section: Discussionmentioning
confidence: 99%
“…All samples studied for this paper were manufactured with process [14,15]. In the IBS process, an ion source accelerates ions with a high kinetic energy onto the target.…”
Section: Materials Properties and Coating Processmentioning
confidence: 99%
“…Comparison of single shot experiments and calculated LIDT of mixture materials Measurements from[15].…”
mentioning
confidence: 99%